Prerequisites for socio-pedagogical support in developing anti-terrorist awareness among university students (Journal of Educational Sciences, 2024)
There are many definitions of terrorism in international scientific practice, but in general, its properties can be characterized as: unpredictability, sophistication of forms, ideological motivation, instability and violence. Tragedies in different countries of the world, for example, the tragic event at Crocus city-hall, and other crisis events actualize programmatic, legal, organizational and pedagogical changes to develop the anti-terrorist consciousness of young people. The key role is played by the awareness of the trainees, the development of their critical and analytical skills, and the level of legal awareness. The article is aimed at a comprehensive study of the prerequisites for countering terrorism in Kazakhstan and an empirical study of the factors contributing to the development of anti-terrorist consciousness among students. Research method: analysis of normative and legal documents and theoretical developments in the field of terrorism and radicalization prevention among young people, focus group research among 1st-4th year students, approximate age 17-21 years.  A total of 4 groups of 12 people (48 people) each were covered by the focus group research. According to the results of the study, students of 1-2 courses see their role in improving religious education and upbringing, strengthening national values and meanings. Students of 3-4 courses in the fight against terrorism and its ideology are more focused on such tools as the development of critical thinking, increased motivation, patriotic education, volunteering and participation in socially significant projects and events.Key words: prevention, terrorism, violence, anti-terrorist values, anti-terrorist attitudes, critical thinking.